Getting the measure of syphilis: qPCR to better understand early infection. Issue 6 (12th July 2011) - Tipple, Craig; Hanna, Mariam O F; Hill, Samantha; Daniel, Jessica; Goldmeier, David; McClure, Myra O; Taylor, Graham P
Abstract : Objectives: Until recently, PCR had been used to detect but not quantify Treponema pallidum . To understand infection kinetics of this uncultivable organism, a real-time PCR assay was developed to quantify 47 kDa membrane lipoprotein gene DNA ( tpp47 ). Methods: Assay specificity was determined against DNA from humans, skin organisms and sexually transmitted pathogens. tpp47 DNA (Nichols strain) was used to construct a standard curve for T pallidum quantification. Blood and ulcer samples were obtained from 99 patients being investigated or screened for syphilis and tpp47 was quantified. Results: The assay was specific, not cross-reactive with other organisms tested and sensitive, with a detection limit of a single copy of tpp47 DNA. For ulcer samples, the assay was 100% sensitive and 97.14% specific. Sensitivity fell to 34.1% for blood samples but specificity remained high (100%). tpp47 DNA was more commonly detected, and at a higher copy number, in blood of patients with secondary infection (sensitivity 57.89%) compared with primary infection. Quantity of tpp47 DNA was higher in primary infection ulcers, especially in HIV-1-positive patients, than in ulcers persisting into secondary disease. Conclusions: Quantifying T pallidum provides insight into syphilis infection kinetics: Ulcers of primary disease in HIV-1-positive patients are perhaps more infectious and the presence and load of T pallidum bacteraemia is variable, with a peak in the secondary stage. Quantitative PCR has the potential to map T pallidum infection and to highlight the impact of HIV on syphilis.